INTEGRATING ENVIRONMENTAL EDUCATION AND CREATIVE ARTS IN EARLY CHILDHOOD: A COMMUNITY DEVELOPMENT INITIATIVE AT BAIT ADZKIA ISLAMIC KINDERGARTEN SCHOOL - Fata, Ferdinan Indra; Kamala, Galang; Sabrina, Absarina Marsya; Putri Cahyono, Patricia Kayla; Lamu, Roberto Megavent; Purwanto, Edi (Jurnal Pengabdian dan Kewirausahaan, 2024)
This paper presents a community development initiative conducted in collaboration with Bait Adzkia Islamic Kindergarten School. A team of five university students undertook the project as part of their Sustainable Development coursework. The initiative's purpose was to engage kindergarten students in creative activities centered on recycling plastic waste into colleges, fostering skills in problem-solving, teamwork, and environmental awareness. The method involved thorough preparation of materials, including collecting and preparing plastic waste, organizing children into groups, and guiding them through the process of creating collages. The results demonstrated significant engagement and satisfaction among the kindergarten students upon completing their artwork, highlighting their enthusiasm and understanding of environmental stewardship. The study's implications underscored the effectiveness of integrating environmental education with creative arts in early childhood settings, promoting sustainable practices and preparing young learners to become responsible global citizens. This initiative contributes to broader discussions on the role of early childhood education in instilling values of environmental sustainability, emphasizing practical applications of theoretical knowledge within community contexts.